2008
DOI: 10.1016/j.nuclcard.2007.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose and cancer risk estimates in 16-slice computed tomography coronary angiography

Abstract: Background-Recent advances have led to a rapid increase in the number of computed tomography coronary angiography (CTCA) studies performed. While several studies have reported effective dose (E), there is no data available on cancer risk for current CTCA protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…Only 3 organs were used for radiogenic cancer LAR assessment, leading to a slight underestimation of the total LAR. According to LAR estimates in 16-slice CCTA, 40 lung and breast cancer account for 84% of all solid cancers in women; for men, lung cancer contributes 79% to solid cancer risk. Uncertainties related to organ dose estimation such as the potential variability of the manual tracing of the organ contours on the original CT images and assumptions inherent in the cancer risk model used inevitably limit the accuracy of the reported results.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 organs were used for radiogenic cancer LAR assessment, leading to a slight underestimation of the total LAR. According to LAR estimates in 16-slice CCTA, 40 lung and breast cancer account for 84% of all solid cancers in women; for men, lung cancer contributes 79% to solid cancer risk. Uncertainties related to organ dose estimation such as the potential variability of the manual tracing of the organ contours on the original CT images and assumptions inherent in the cancer risk model used inevitably limit the accuracy of the reported results.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to ionizing radiation is a significant limitation of this technology. [5][6][7][8] Substantial cumulative doses because of repeated testing is concerning for increased lifetime attributable risk of cancer. 9,10 However, radiation dose from coronary CTA can be substantially reduced with specific scanner hardware acquisition protocols.…”
mentioning
confidence: 99%
“…The prospective gating technique is applied to patients with low heart rates (<70 bpm) and average BMI only to minimise the risk of artefacts that would prove impossible to eliminate given the small number of phases available. In our view, the need to administer beta-blockers -once again, a need that dual-source technology had considerably reduced -is an acceptable price to pay for a significant reduction in the radiation dose delivered, particularly to young patients [26,27]. A recent study, however, has shown that prospective gating can also be used with DSCT in patients with heart rates >70 bpm [28].…”
Section: Discussionmentioning
confidence: 99%
“…Infatti, la tecnica di sincronizzazione prospettica viene applicata attualmente in pazienti con frequenze basse (inferiori ai 70 bpm) e con un BMI non elevato, al fine di ridurre al minimo la possibilità di artefatti che, data il basso numero di fasi a disposizione, non sarebbe possibile eliminare. A nostro giudizio la necessità di betabloccare nuovamente i pazienti, che sembrava essersi notevolmente ridotta con l' avvento della tecnologia dual source, ci sembra un prezzo accettabile da pagare a fronte di una significativa riduzione della dose somministrata, in particolare nei soggetti giovani [26,27]. Un recente studio ha dimostrato tuttavia la possibilità di utilizzare il protocollo prospettico anche in pazienti con frequenze cardiache superiori ai 70 bpm con TCDS [28].…”
Section: Discussionunclassified